2018
DOI: 10.1002/2018jd028304
|View full text |Cite
|
Sign up to set email alerts
|

Tritium Records to Trace Stratospheric Moisture Inputs in Antarctica

Abstract: Better assessing the dynamic of stratosphere‐troposphere exchange is a key point to improve our understanding of the climate dynamic in the East Antarctica Plateau, a region where stratospheric inputs are expected to be important. Although tritium (3H or T), a nuclide naturally produced mainly in the stratosphere and rapidly entering the water cycle as HTO, seems a first‐rate tracer to study these processes, tritium data are very sparse in this region. We present the first high‐resolution measurements of triti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 56 publications
5
28
0
Order By: Relevance
“…Such similarities are also evidenced when comparing Na + concentration to 10 Be concentration along the same snow pit (Baroni et al, ; Figures c and d) and have likewise been identified with 3 H (Fourré et al, ). It has been proposed that these periodicities within the 3‐ to 7‐year band result from a modulation of atmospheric circulation in the troposphere, induced either by the Antarctic Circumpolar Wave (ACW; Baroni et al, ) or by the Southern Annular Mode (SAM; Fourré et al, ). In this scenario, the coupling between 10 Be/ 3 H and Na + is seen as an indirect link related to the influence of modes of atmospheric circulation (ACW or SAM) on stratospheric inputs (Baroni et al, ; Fourré et al, ).…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…Such similarities are also evidenced when comparing Na + concentration to 10 Be concentration along the same snow pit (Baroni et al, ; Figures c and d) and have likewise been identified with 3 H (Fourré et al, ). It has been proposed that these periodicities within the 3‐ to 7‐year band result from a modulation of atmospheric circulation in the troposphere, induced either by the Antarctic Circumpolar Wave (ACW; Baroni et al, ) or by the Southern Annular Mode (SAM; Fourré et al, ). In this scenario, the coupling between 10 Be/ 3 H and Na + is seen as an indirect link related to the influence of modes of atmospheric circulation (ACW or SAM) on stratospheric inputs (Baroni et al, ; Fourré et al, ).…”
Section: Resultssupporting
confidence: 60%
“… 36 Cl evolution through time (a) from this study (green line) compared to 36 Cl concentration of Vostok in another snow pit dug and measured 10 years prior to our study (Delmas et al, , in black) and also in comparison with 137 Cs (b) (Baroni et al, ) and 3 H (c) (Fourré et al, ) from the same snow pit. The 36 Cl model simulation is also represented, with the orange line reflecting the values of advection and diffusion proposed by Delmas et al, , the red line illustrating new parameters fitting better with our 36 Cl values, and the purple line representing a reduced diffusion coefficient compared to the other two simulations.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations